Peran Reserse dalam Penyidikan Tindak Pidana Pencurian dengan Pemberatan (Studi Kasus Polsek Sukawati Gianyar Bali) - Kadek Bayu Krisna Juliantara; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2021)
Recently, the incidence of criminal acts of theft with weights has increased, the investigator in handling this case must be careful in uncovering criminal acts of theft with weights. This study aims to examine the role of the detective in uncovering the crime of theft by weighting and analyzing the obstacles of the investigator in uncovering the crime of theft by weight. The type of research used is empirical, namely research based on facts that occur and develop existing concepts, the approach method used is by conducting research in the field. The sources of legal materials used are primary and secondary legal materials obtained through observation and documentation. After all the data has been collected, the next step is to process and analyze it qualitatively. The results showed that the role of the criminal investigator of the Sukawati Police in uncovering the criminal act of theft of weighting began with a complaint report from the public, then the action of the Sukawati Police Detective carried out an examination at the scene of the case, examination of witnesses, confiscation of evidence, arrest, search, detention, filing. and submission of case files to the court. The obstacles faced by the Criminal Investigation Unit of the Sukawati Sector are the perpetrator, a recidivist, the lack of tools to track the perpetrators, and community factors.